Find the derivative of f(t) = csch t (1-ln csch t)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to use the product rule to find the derivative of f(t) such that:

`f'(t) = (cosech t)'(1 - ln cosech t) + (cosech t)(1 - ln cosech t)'`

`f'(t) = cosech t*cotanh t*(1 - ln cosech t) + (cosech t)(-(cosech t)')/(cosech t)`

`f'(t) = cosech t*cotanh t*(1 -...

Unlock
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial

You need to use the product rule to find the derivative of f(t) such that:

`f'(t) = (cosech t)'(1 - ln cosech t) + (cosech t)(1 - ln cosech t)'`

`f'(t) = cosech t*cotanh t*(1 - ln cosech t) + (cosech t)(-(cosech t)')/(cosech t)`

`f'(t) = cosech t*cotanh t*(1 - ln cosech t) - cosech t*cotanh t`

You need to factor out `cosech t*cotanh t`  such that:

`f'(t) = cosech t*cotanh t(1 - ln cosech t - 1)`

`f'(t) = -cosech t*cotanh*ln cosech t`

Hence, evaluating the derivative of the given function yields `f'(t) = -cosech t*cotanh*ln cosech t` .

Approved by eNotes Editorial Team